Provision Study of Lactobacillus spp. and Barley Straw Against Dynamics of DO, pH and Plankton Abundance - Silvi Hardiyana; Boedi Rahardja Setya Rahardja; EndangMasithah Dewi Masithah (Journal of Marine and Coastal Science, 2020)
Fish farming activities in recent years, many shows water quality conditions do not support fish life are maintained optimally and decreases the carrying capacity, one DO and pH parameters. As a remedial action is carried out either by probiotic bacteria One commonly used in the application of probiotics is Lactobacillus spp. Gram positive bacterium Lactobacillus spp. widely used as probiotics to improve the quality of air Penggunaan Lactobacillus spp. is expected to improve the quality of water that is accelerating the overhaul of organic material in the water and suppress harmful microorganisms that can affect the dynamics of DO, pH and increasing nutrient waters. Barley straw is a powdered extract of hay-producing H2O2 which serves to inhibit the growth of microalgae. The use of straw extract powder has become more common as an alternative method for controlling excessive algae growth by blocking and not get rid of it so that stabilization of the abundance of plankton in the water can be controlled well.To study the role of Lactobacillus spp. and barley straw in the management of organic matter and plankton abundance Giving a research study Lactobacillus spp. and barley straw to the dynamics of DO, pH and Abundance of Plankton.